Endoplasmic reticulum stress/autophagy pathway is involved in diabetes-induced neuronal apoptosis and cognitive decline in mice - Kong, Fei-Juan; Ma, Lei-Lei; Guo, Jun-Jie; Xu, Lin-Hao; Li, Yun; Qu, Shen (Clinical science (1979), 2018)
Diabetes mellitus is a significant global public health problem depicting a rising prevalence worldwide. As a serious complication of diabetes, diabetes-associated cognitive decline is attracting increasing attention. However, the underlying mechanisms are yet to be fully determined. Both endoplasmic reticulum (ER) stress and autophagy have been reported to modulate neuronal survival and death and be associated with several neurodegenerative diseases. Here, a streptozotocin-induced diabetic mouse model and primary cultured mouse hippocampal neurons were employed to investigate the possible role of ER stress and autophagy in diabetes-induced neuronal apoptosis and cognitive impairments, and further explore the potential molecular mechanisms. ER stress markers GRP78 and CHOP were both enhanced in diabetic mice, as was phosphorylation of PERK, IRE1α, and JNK. In addition, the results indicated an elevated level of autophagy in diabetic mice, as demonstrated by up-regulated expressions of autophagy markers LC3-II, beclin 1 and down-regulated level of p62, and increased formation of autophagic vacuoles and LC3-II aggregates. Meanwhile, we found that these effects could be abolished by ER stress inhibitor 4-phenylbutyrate or JNK inhibitor SP600125 in vitro. Furthermore, neuronal apoptosis of diabetic mice was attenuated by pretreatment with 4-phenylbutyrate, while aggravated by application of inhibitor of autophagy bafilomycin A1 in vitro. These results suggest that ER stress pathway may be involved in diabetes-mediated neurotoxicity and promote the following cognitive impairments. More important, autophagy was induced by diabetes possibly through ER stress-mediated JNK pathway, which may protect neurons against ER stress-associated cell damages.